Pembelajaran Cinta Lingkungan Berdasarkan Pembentukan Karakter dan Penerapan Konsep 3R - Revo Gilang Firdaus (Simposium Nasional Mulitidisiplin (SinaMu), 2020)
Environmental conditions in Indonesia and even in the world continue to deteriorate over time. The application of community education, especially for children to love the environment, is considered to be a positive thing that needs to be applied. Therefore, the aim of this research is to explore child-friendly methods by applying the 3R (reuse, reduce, recycle) concept which has an impact on the formation of good character for children, especially in the fields of creativity and love for the environment. In its implementation, this project takes place in collaboration with YFCC Indonesia and the CCE Community and takes place in the Kebagusan area with a total of 20-25 children. The analysis technique used is descriptive analytic obtained from observation and documentation during the learning process. The results of this study indicate that the learning method that is easy to understand by children and attractive in its presentation gives a positive impression and gets high enthusiasm from the children. In addition, the increase in creativity can also be seen due to the absence of restrictions in doing the assigned tasks so that children can be creative.